Misinformation and professional news on largely unmoderated platforms: the case of telegram - Herasimenka, A; Bright, J; Knuutila, A; Howard, P (Taylor and Francis, 2022)
To date, there is little research to measure the scale of misinformation and understand how it spreads on largely unmoderated platforms. Our analysis of 200,000 Telegram posts demonstrates that links to known sources of misleading information are shared more often than links to professional news content, but the former stays confined to relatively few channels. We conclude that, contrary to popular received wisdom, the audience for misinformation is not a general one, but a small and active community of users. Our study strengthens an empirical consensus regarding the spread of misinformation and expands it for the case of Telegram.